The Effect of Transaction Experience Using Digital Wallets on User Satisfaction in Millennial Generation - Purnama, Suryari; Bangun, Cicilia Sriliasta; A. Faaroek, Safiani (Pandawan, 2021)
The purpose of this study to determine the effect after transaction failure and after failure recovery on the transaction experience, the effect after transaction failure and recovery from transaction failure using digital wallets on user satisfaction, especially in the millennial generation. The population of this study is all digital wallet users in the DKI Jakarta province with a total sample of 94 digital wallet users. The sampling method uses purposive sampling with the criteria of digital wallet users who have made transactions for at least 1 year, this is intended so that these respondents already have transaction experience and are at least 17 years old. Meanwhile, the data processing used Structural Equation Modeling analysis software Lisrel. The results showed: (1) Transaction failure affects the transaction experience of digital wallet users; (2) Transaction failure recovery will affect the transaction experience of digital wallet users; (3) Transaction experience affects the satisfaction of digital wallet users; (4) Transaction failure has no effect on digital wallet user satisfaction; (5) Transaction failure recovery affects the satisfaction of digital wallet users. The novelty of this research is transaction failure has no effect on digital wallet user satisfaction. In addition, the benefits that are felt are far greater than the failures that are experienced, especially when recovery from failure is carried out quickly and precisely.